A novel MECOM gene variant causes severe thrombocytopenia in a neonate: a case report and review of the literature - Jiaxin Li; Ting Peng; Guoqiang Cheng; Lin Yang; Jianguo Zhou; Rong Zhang; Peng Zhang (Journal of Medical Case Reports)
Abstract Background Mutations in the MECOM gene have been recognized as a causative factor in MECOM-associated syndrome, which encompasses a spectrum of hematologic and extra-hematologic manifestations. Hematologic features range from isolated thrombocytopenia to severe bone marrow failure, while extra-hematologic manifestations may include skeletal, cardiac, renal, and other abnormalities. Here, we present a case of a Han Chinese newborn with a previously unreported variant in the MECOM gene. Case presentation We report a 0-day-old female Han Chinese neonate who presented with severe thrombocytopenia and intracranial hemorrhage, ultimately succumbing to multiple organ failure and intracranial hemorrhage on the third day after birth. Genetic sequencing identified a heterozygous frameshift variant, c.157_158del, within the MECOM gene. This variant led to a substitution of the 53rd amino acid from methionine to glycine, terminating at the 54th amino acid. A comprehensive review of literature indicated that MECOM gene mutations included missense (68.3%), deletion (8.5%), splice site (8.5%), frameshift (7.3%), and nonsense (7.3%) mutations. Patients with missense mutations frequently exhibited radioulnar synostosis, while bone marrow failure was more commonly associated with the other four types of mutations. Conclusion This study adds a novel variant of the MECOM gene to the current body of knowledge. In addition, we provide a comprehensive summary of previously reported cases. This case expands the phenotypic spectrum of MECOM variants and underscores the potential for rapid progression to a life-threatening condition.